2003
DOI: 10.1128/jvi.77.1.309-317.2003
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Human Parainfluenza Virus Type 3 Hemagglutinin-Neuraminidase Causing Increased Receptor Binding Activity and Resistance to the Transition State Sialic Acid Analog 4-GU-DANA (Zanamivir)

Abstract: Entry and fusion of human parainfluenza virus type 3 (HPF3) require the interaction of the viral hemagglutinin-neuraminidase (HN) glycoprotein with its sialic acid receptor. 4-GU-DANA, a potent inhibitor of influenza virus neuraminidase, inhibits not only HPF3 neuraminidase but also the receptor binding activity of HPF3 HN and thus its ability to promote attachment and fusion. We previously generated a 4-GU-DANAresistant HPF3 virus variant (ZM1) with a markedly fusogenic plaque morphology that harbored two HN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
103
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(107 citation statements)
references
References 26 publications
4
103
0
Order By: Relevance
“…In Nipah and Hendra viruses, attachment proteins can be used interchangeably, which suggests slightly different F and HN interaction mechanisms among these paramyxoviruses (3). However, no final conclusion has yet been reached on the pattern of interaction between HN and F proteins (4,11,12,14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Nipah and Hendra viruses, attachment proteins can be used interchangeably, which suggests slightly different F and HN interaction mechanisms among these paramyxoviruses (3). However, no final conclusion has yet been reached on the pattern of interaction between HN and F proteins (4,11,12,14).…”
Section: Introductionmentioning
confidence: 99%
“…When NDV infects the host cells, the attachment protein first binds to the sialic acid on the cell surface, and then triggers the fusion (4,5). It has been reported that behavior of the receptor-binding promotes dramatic conformational changes of the F protein, which facilitate the membrane fusion process.…”
Section: Introductionmentioning
confidence: 99%
“…While 4-GU-DANA inhibits HPIV neuraminidase activity, it does not prevent release of virus from the infected cell surface (45) as it does in the case of influenza viruses; instead, it blocks interaction between the parainfluenza HN protein and its receptor and thus - surprisingly - aids in the release of newly assembled virions from the infected cell (18). However, by interfering with HN-receptor interaction, 4-GU-DANA blocks receptor binding and thereby blocks fusion and viral entry (18,45). These findings have stimulated interest in designing binding/entry inhibitors for treatment of paramyxovirus infection.…”
Section: Use Of Variant Hn Proteins To Scrutinize the Hn-triggered F mentioning
confidence: 99%
“…The structure of the globular head region is shown in Figure 4A complexed with sialic acid. A single alteration in the HN protein - T193I - leads to an HPIV3 variant with phenotypic resistance to the effects of 4-GU-DANA in terms of both neuraminidase activity and receptor binding (45). Increased receptor-binding avidity alone can confer drug resistance and indeed accounts for part of the variant virus's 4-GU-DANA-resistant properties (45).…”
Section: Properties Of the Hn Protein That Modulate Its Ability To Trmentioning
confidence: 99%
See 1 more Smart Citation